Assessment of tobacco imagery and compliance with tobacco-free rules in popular Indian films. Issue 1 (16th February 2019) - Kulkarni, Muralidhar M; Kamath, Veena Ganesh; Cranwell, Jo; Britton, John; Nazar, Gaurang P; Arora, Monika; Ballal, Kirthinath; Kamath, Asha
Abstract : Background: Exposure to smoking in films causes smoking uptake among adolescents. Investigation of the extent to which tobacco imagery appears, or tobacco control laws are complied with in Indian films is limited, and especially so for films in regional languages. This study presents an analysis of tobacco content and compliance with tobacco control laws in popular films in several languages from the Karnataka state of India. Methods: We used 5 min interval coding to measure actual tobacco use, implied tobacco use, tobacco paraphernalia and tobacco branding in the top 10 films identified from national box office ratings and regional distributor reports in Karnataka in 2015 and 2016. We also assessed compliance with tobacco-free film rules in India. Findings: A total of 47 films, in English, Hindi, Malayalam, Tamil, Telugu and Tulu languages were coded. Any tobacco imagery was observed in 72% of films, and actual tobacco use in 50%. Tobacco imagery was equally prevalent in films classified as suitable for universal viewing (U category) or at age 12 or more (U/A category) films; and significantly more common in films made in regional than national language (Hindi). None of the films were fully compliant with legal requirements on health spots, audiovisual disclaimers and health warnings. Conclusions: Tobacco content was common in films classified as suitable for viewing by children, more among regional than national languages. Compliance with tobacco control laws was low. Stricter enforcement of tobacco-free film rules will protect children and adolescents from exposure to tobacco use on screen.